2019
DOI: 10.1167/tvst.8.3.56
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Loss of Human Vitreal Viscoelasticity

Abstract: Purpose To determine the viscoelasticity of human vitreous bodies and its changes with age in order to benefit the understanding and therapy of vitreoretinal diseases. Methods In a postmortem study, 190 human vitreous bodies were extracted from 33- to 92-year-old donors, analyzed with regard to their viscoelastic properties via dynamic mechanical analyses, and compared with bovine and porcine vitreous. Postmortem intervals and donor-related parameters were examined as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 34 publications
(73 reference statements)
1
32
0
1
Order By: Relevance
“…However, stiff hydrogels can be difficult to inject through a small gauge needle into the vitreous chamber. The storage and loss moduli of synthetic hydrogels 34,[59][60][61][62]69,73,74,76,[81][82][83] (G' = 1203 ± 755 Pa, n = 18 and G" = 373 ± 330 Pa, n = 12) and semisynthetic hydrogels [92][93][94]97,98,[100][101][102]104 (G' = 1330 ± 1090 Pa, n = 9 and G" = 291 ± 223 Pa, n = 9) are approximately two orders of magnitude higher, while natural hydrogels' 37,110 (G' = 99.4 ± 53.4 Pa, n = 3 and G" = 51.5 ± 48.5 Pa, n = 2) are about one order of magnitude higher compared to the human vitreous [15][16][17] (G' = 5.09 ± 1.86 Pa, n = 3 and G" = 1.81 ± 0.98 Pa, n = 3). Hydrogels with different mechanisms of injection into the eye also have a wide variation in storage and loss moduli ( Table 5 and Figure 4B).…”
Section: The Strive For Improved Vitreous Substitutes and Intraocularmentioning
confidence: 95%
See 1 more Smart Citation
“…However, stiff hydrogels can be difficult to inject through a small gauge needle into the vitreous chamber. The storage and loss moduli of synthetic hydrogels 34,[59][60][61][62]69,73,74,76,[81][82][83] (G' = 1203 ± 755 Pa, n = 18 and G" = 373 ± 330 Pa, n = 12) and semisynthetic hydrogels [92][93][94]97,98,[100][101][102]104 (G' = 1330 ± 1090 Pa, n = 9 and G" = 291 ± 223 Pa, n = 9) are approximately two orders of magnitude higher, while natural hydrogels' 37,110 (G' = 99.4 ± 53.4 Pa, n = 3 and G" = 51.5 ± 48.5 Pa, n = 2) are about one order of magnitude higher compared to the human vitreous [15][16][17] (G' = 5.09 ± 1.86 Pa, n = 3 and G" = 1.81 ± 0.98 Pa, n = 3). Hydrogels with different mechanisms of injection into the eye also have a wide variation in storage and loss moduli ( Table 5 and Figure 4B).…”
Section: The Strive For Improved Vitreous Substitutes and Intraocularmentioning
confidence: 95%
“…30 The assumptions used in their analytical model (homogeneous and spherical vitreous), limited image resolution, and patient compliance might explain the high standard deviation (300 ± 100 Pa) and drastic difference from the moduli directly measured using shear rheology on in vitro dissected vitreous samples reported by other studies. [15][16][17] However, to the best of the authors' knowledge, Piccirelli et al (2012) is the first study that reported the in vivo storage and loss moduli of the human vitreous humor. It is likely that the measured moduli from in vitro and ex vivo experiments are slightly lower than in vivo due to tissue degradation and destruction of the tissue architecture during testing.…”
Section: Studies On the Mechanical Properties Of The Vitreous Humormentioning
confidence: 99%
“…Rheological experiments showed viscoelastic properties of the PEGDA and PEGDA‐ co ‐PEGMA hydrogels similar to the native tissue . The linear viscoelastic region for both hydrogels was determined to be below 10% strain ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…The storage modulus ( G ′) and loss modulus ( G ″) of both hydrogels were in the same order of magnitude as the natural human vitreous (Figure 3B). The storage modulus of the human vitreous ranges from 1 to 7 Pa, whereas its loss modulus ranges from 0.3 to 1 Pa . The storage and loss moduli of the PEGDA hydrogel were statistically larger than those of the natural human vitreous with the storage modulus ranging from 5 to 11 Pa and the loss modulus averaging 0.9 Pa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation